The Six Sigma handbook : a complete guide for green belts, black belts, and managers at all levels - Pyzdek, Thomas
"This thoroughly revised, industry-standard guide delivers all the information you need to apply Six Sigma techniques and dramatically improve processes, profitability, sustainability, and long-term growth. Written by two of the foremost authorities in Six Sigma, the book shows you, step by step, how to build the best teams and foster effective leadership while maximizing customer satisfaction and boosting profits. This new edition features a number of important updates, including AI, big data and machine learning, mind mapping, healthcare statistics, and modern supply chain challenges. This hands-on resource also lays out cutting-edge applications for social media data, decision trees, remote technology, and web scrapers"--